Role of Endoscopic Biliary Stenting in the Management of Difficult Common Bile Duct Stones - Nimai Das; Chinmoy Saha; Shishir Sikto Sarker; Dr Tasmia Tanjum; Sanghita Ghose; Chanchal Kumar Ghosh (Research Synergy Foundation, 2025)
Removing large or multiple common bile duct stones that cannot be cleared at first endoscopic retrograde cholangiopancreatography (ERCP) is difficult in resource-limited settings. This study assessed whether temporary plastic stenting promotes subsequent clearance of these “difficult” stones. In a prospective observational study at Bangabandhu Sheikh Mujib Medical University, Dhaka (November 2019 – March 2021), 35 adults with difficult common bile duct stones underwent endoscopic sphincterotomy followed by placement of a 7–10 Fr plastic stent. Stone size, number, index, and duct diameter were measured before stenting and at repeat ERCP three months later. Clearance rates and stent-related adverse events were recorded. Thirty-one patients completed follow-up. Mean stone size fell from 19.1 ± 2.1 mm to 15.8 ± 3.1 mm; mean stone number from 1.80 ± 0.74 to 1.45 ± 0.67; and mean stone index from 28.9 ± 9.2 mm to 20.9 ± 9.9 mm (all p < 0.001). Complete bile duct clearance at second-session ERCP was achieved in 69.7%, while 6.1% showed spontaneous passage. Complications were limited to stent migration (6%), occlusion (9%), and cholangitis (6%), with no procedure-related mortality. Short-term endoscopic biliary stenting safely reduces stone burden and enables successful second-session extraction in most patients with difficult common bile duct stones. It offers an effective bridge therapy where advanced lithotripsy techniques are unavailable.